PUBLIC SENTIMENT ANALYSIS OF 'DIRTY VOTE' DOCUMENTARY FILM ON TWITTER USING NAÏVE BAYES WITH GRID SEARCH OPTIMIZATION - Bagaskara, Febrian Chrissma; Syahrullah, Syahrullah; Hendra, Andi; Lamasitudju, Chairunnisa; Rinianty, Rinianty (Informatika, Universitas Jenderal Soedirman, 2024)
The film